THE IMPLEMENTATION OF NUMBERED HEADS TOGETHER IN TEACHING READING RECOUNT TEXTS TO THE TENTH GRADERS IN SMA NEGERI 1 KEDUNGPRING LAMONGAN (RETAIN, 2015)
Abstract This study deals with the implementation of Numbered Heads Together in teaching reading recount texts to the tenth graders. The objectives of this study are: (1) to describe how the teacher implements “Numbered Heads Together” in teaching reading recount texts to the tenth graders, and (2) to describe the students’ attitudes toward the implementation of Numbered Heads Together in teaching reading recount texts. This research used descriptive qualitative research design. The technique was implemented in X-IIS 3 class of SMAN 1 Kedungpring Lamongan. To get the data of the study the researcher used two instruments. They were observation sheets and questionnaires. These analysis of the data showed that the teacher followed the procedures of Numbered Heads Together technique in teaching reading recount texts, and the students also participated during the implementation of Numbered Heads Together technique. The students’ attitudes showed that they reacted positively towards the implementation of the technique. In conclusion, Numbered Heads Together technique can be implemented in teaching reading because it helped the students read a recount text. There were many students of X-IIS 3 in SMAN 1 Kedungpring Lamongan agreed that they were enjoying the teaching and learning process when the technique was implemented. Since the teacher could modify the technique to make the students get more interested. Keywords: reading, Numbered Heads Together, recount texts Abstrak Penelitian ini berhubungan dengan penerapan Numbered Heads Together dalam pengajaran membaca teks recount untuk kelas sepuluh. Tujuan penelitian ini adalah: (1) untuk mendeskripsikan bagaimana guru menerapkan Numbered Heads Together, dan (2) untuk mendeskripsikan sikap siswa terhadap penerapan Numbered Heads Together dalam pengajaran membaca teks recount. Penelitian ini menggunakan desain penelitian deskriptif kualitatif. Teknik ini diimplementasikan pada kelas X-IIS 3 di SMAN 1 Kedungpring Lamongan. Untuk mendapatkan data penelitian, peneliti menggunakan dua instrument, lembar observasi dan kuesioner. Data tersebut menunjukkan bahwa guru mengikuti prosedur Numbered Heads Together teknik dalam aktifitas membaca siswa, dan siswa juga berpartisipasi dalam pelaksanaan teknik tersebut. Sikap siswa menunjukkan bahwa mereka bereaksi positif terhadap pelaksanaan teknik. Kesimpulannya, Numbered Heads Together teknik dapat diimplementasikan dalam pengajaran membaca karena dapat membantu siswa dalam memahami teks bacaan recount. Ada banyak siswa dari kelas X-IIS 3 di SMA Negeri 1 Kedungpring Lamongan setuju bahwa mereka menikmati proses belajar dan mengajar ketika teknik diimplementasikan. Karena guru dapat memodifikasi teknik untuk membuat siswa lebih tertarik.. Kata Kunci: membaca, Numbered Heads Together, teks recount.